THE INFLUENCE OF NATIONAL AND CULTURAL FACTORS ON THE AUDIENCE’S PERCEPTION OF AN IRONIC SPEECH ACT - Abduqodirova Madina Abduqayum qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. This study examines how national and cultural factors influence the audience’s perception and interpretation of ironic speech acts. It emphasizes that irony is culturally dependent and not universally understood. The research explores how differences in cultural background, communication styles, and values affect the recognition of irony. The findings contribute to the fields of pragmatics, intercultural communication, and linguistic anthropology.